Pattern Recognition in Astrophysics and the Anthropic Principle - Darg, D (2012)
The role of the Anthropic Principle in astrophysics and cosmology is examined in two principal parts. The first (minor) part takes a chiefly philosophical perspective and examines the manner in which human cognition features into discussions on cosmic origins. It is shown that the philosophical questions raised by the Anthropic Principle and ‘fine-tuning of life’ bear resemblances to problems within the philosophy of mind and we seek a common origin for this surprising parallel. A form of ‘epistemic structural realism’ is defended and used to critique the physicalist identity thesis. It is argued that equating ‘reality’ with mathematical structures, which is the basis of the identity thesis, leads to incoherent conclusions. Similar reasoning is used to critique infinite Multiverse theories. In the second (major) part, we gradually transition into mainstream astrophysics, first presenting a new line of research to explore counterfactual universes using semi-analytic models (SAMs) and offering a preliminary study wherein the cosmological constant is varied and the effects on ‘advanced civilisations’ are examined. The importance of galaxy mergers is highlighted and leads to their study. We first try solving the pattern-recognition problem of locating mergers using the Galaxy Zoo database and produce the largest homogenous merger catalogue to date. We examine their properties and compare them with the SAMs of the Millennium Simulation finding good general agreement. We develop the Galaxy Zoo approach with a new visual-interface design and double the size of the merger catalogue of SDSS mergers in the local Universe.